KORELASI MINAT BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN BERPIKIR SISWA KELAS VI KECAMATAN GEMAWANG - Susilo Wardani, Haning; Mashar, Riana; Imam Farisi, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Class VI students in Gemawang District, Temanggung Regency, Central Java Province, have less than optimal thinking skills in learning. It was proven in the results of the national exam for the 2018/2019 school year that it was ranked 9th out of 20 sub-districts. The aim of this research is to determine whether interest in learning and learning independence have a positive correlation with thinking ability. This research was conducted on class VI students in Gemawang District, Temanggung Regency, Central Java Province with a population of 415 students. The sample used was 81 students. The sample size in this study was determined using the Taro Yamane or Slovin formula at a significance level of 10%. The sampling technique was simple random sampling. The independent variables studied were interest in learning and learning independence, then the dependent variable studied was thinking ability. The instrument used was a questionnaire. All questionnaires have been tested for validity and reliability. The questionnaire reliability test formula uses Cronbach's Alpha. It can be seen that the reliability value for the thinking ability questionnaire is 0.922; interest in learning 0.900; and learning independence 0.853. Collecting data on students' interest in learning, learning independence and thinking abilities by giving questionnaires to students via Google Form, considering that it is still during the pandemic. Data were analyzed using descriptive statistics with a correlation test using the IBM SPSS Statistics Subscription 28.0.1.0 program. (142) From the research results it is known that interest in learning is positively correlated with students' thinking abilities, this is proven by the Sig. equal to 0.000 < 0.05. Learning independence has a positive correlation with students' thinking abilities, this is proven by the Sig value. equal to 0.000 < 0.05. And learning interest and learning independence together can have a positive correlation with students' thinking abilities, this is proven by a significance value of 0.000 < 0.05.